2022
DOI: 10.1002/ejoc.202200153
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Vinylene Carbonates from Aromatic Aldehydes**

Abstract: Substituted vinylene carbonates were directly prepared from aromatic aldehydes following a one‐pot Benzoin condensation/transcarbonation sequence under solvent‐free conditions. The combination of a N‐phenyl substituted triazolium salt NHC precursor and 4‐dimethylaminopyridine (DMAP) was found essential to reach high yield and selectivity. The reaction scope was investigated with a range of aromatic aldehydes and the corresponding vinylene carbonates were obtained with 32–86 % isolated yields (14 examples).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…The ketone‐carbonate species in the work of Duguet's group was shown to be the key intermediate for the preparation of endo ‐VCs [18,19] . At the same time, exo ‐VCs are reported to yield these ketones through the ring‐opening reaction with several nucleophiles [5a,7a] .…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The ketone‐carbonate species in the work of Duguet's group was shown to be the key intermediate for the preparation of endo ‐VCs [18,19] . At the same time, exo ‐VCs are reported to yield these ketones through the ring‐opening reaction with several nucleophiles [5a,7a] .…”
Section: Resultsmentioning
confidence: 98%
“…The ketone-carbonate species in the work of Duguet's group was shown to be the key intermediate for the preparation of endo-VCs. [18,19] At the same time, exo-VCs are reported to yield these ketones through the ring-opening reaction with several nucleophiles. [5a,7a] Therefore, our hypothesis was that with a suitable catalytic system based on an alcohol and a base for a reversible ring-opening, exo-VCs could be transferred into the corresponding endo-VCs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…34 Recently, our group has demonstrated that diphenyl carbonate (DPC) can be used as a cheap and non-toxic carbonyl source for the preparation of vinylene carbonates from either benzoins/acyloins 35 or directly from aldehydes. 36 Based upon these previous studies, we now report here our results on the preparation of vinylene carbonates using poly(bisphenol A carbonate) as a carbonyl source, thus concomitantly leading to the chemical upcycling of this polymer (Fig. 1).…”
Section: Introductionmentioning
confidence: 79%